Computerized adventitious respiratory sounds as outcome measures for respiratory therapy: a systematic review - Marques, Alda (2014)
There is a need to develop simple, noninvasive, and sensitive outcome measures for respiratory therapy. Adventitious respiratory sounds (ie, crackles and wheezes) can be objectively characterized with computerized respiratory sound analysis (CORSA) and have been shown to contribute for diagnosis purposes; however, their potential for use as outcome measures is unknown. Thus, this systematic review synthesizes the evidence on the use of computerized adventitious respiratory sounds as outcome measures. METHODS: The Web of Knowledge, MEDLINE, EMBASE, and SCOPUS databases were searched. Reviewers independently selected studies according to the eligibility criteria. Effect sizes and 95% CIs were computed. RESULTS: Twelve studies with different designs (observational, n = 3; quasi-experimental n = 7; and randomized controlled trial, n = 2) were included. Eight studies were conducted with adults, and 4 studies with children. Most studies explored only one type of adventitious respiratory sound. For wheezes, the occupation rate seemed to be the most promising parameter to be used as an outcome measure, with high/medium effect sizes (0.62-1.82). For crackles, the largest deflection width showed high effect sizes (1.31 and 1.04); however, this was explored in only one study. Crackle number and 2-cycle duration presented conflicting information, with high/poor effect sizes depending on the study. CONCLUSIONS: Specific variables of each adventitious respiratory sound detected and characterized by CORSA showed high effect sizes and, thus, the potential to be used as outcome measures. Further research with robust study designs and larger samples (both of children and adult populations), and following CORSA guidelines is needed to build evidence-based knowledge on this topic.